Transformasi Digital Sistem Perpajakan : Dampaknya terhadap Kepatuhan Pajak Usaha Mikro, Kecil dan Menengah: Studi pada UMKM Sektor Informal di Kota Makassar - Nur Wahyuni; Hasnidar Syam; Syamsu Alam; Eka Ariaty Arfah (Al-Buhuts, 2025)
Digital transformation of the tax administration through DJP Online, e-Filing, and e-Billing is expected to enhance efficiency, transparency, and access to tax services. However, among informal-sector MSMEs, the benefits are not evenly realized, as a persistent gap remains between revenue potential and actual collections, shaped by limited digital literacy, low tax understanding, and constraints in infrastructure and technological readiness. This study aims to examine the impact of digital tax transformation on tax compliance among informal-sector MSMEs in Makassar City, identify key barriers to adopting digital tax systems, and formulate context-sensitive adaptive strategies to strengthen the effectiveness of digitalization policies. A qualitative approach with an exploratory case-study design was employed using in-depth interviews, participant observation, focus group discussions, and document analysis; data were analyzed thematically and triangulated to capture MSMEs’ responses, perceptions, and compliance behaviors. The findings indicate that digital tax transformation contributes positively to formal compliance particularly timely filing and easier tax payments yet this improvement is not fully matched by stronger material compliance due to ongoing limitations in digital literacy, regulatory understanding, and perceived system complexity, highlighting the need for sustained education and assistance. Moreover, when digital services are perceived as user-friendly, fair, and high-quality, some MSME taxpayers show a shift from enforced compliance toward voluntary compliance.